Differential solvation of intrinsically disordered linkers drives the formation of spatially organized droplets in ternary systems of linear multivalent proteins. (12th April 2018) - Harmon, Tyler S; Holehouse, Alex S; Pappu, Rohit V
Abstract: Intracellular biomolecular condensates are membraneless organelles that encompass large numbers of multivalent protein and nucleic acid molecules. The bodies assemble via a combination of liquid–liquid phase separation and gelation. A majority of condensates included multiple components and show multilayered organization as opposed to being well-mixed unitary liquids. Here, we put forward a simple thermodynamic framework to describe the emergence of spatially organized droplets in multicomponent systems comprising of linear multivalent polymers also known as associative polymers. These polymers, which mimic proteins and/or RNA have the architecture of domains or motifs known as stickers that are interspersed by flexible spacers known as linkers. Using a minimalist numerical model for a four-component system, we have identified features of linear multivalent molecules that are necessary and sufficient for generating spatially organized droplets. We show that differences in sequence-specific effective solvation volumes of disordered linkers between interaction domains enable the formation of spatially organized droplets. Molecules with linkers that are preferentially solvated are driven to the interface with the bulk solvent, whereas molecules that have linkers with negligible effective solvation volumes form cores in the core–shell architectures that emerge in the minimalist four-component systems. Our modeling has relevance for understanding the physical determinants of spatially organized membraneless organelles.